PENGGUNAAN NaHSO3 DAN H2O2 UNTUK MENGURANGI KONSENTRASI FORMALDEHID PADA LIMBAH CAIR PENYAMAKAN FORMALDEHID KULIT GOLF SNOW WHITE - Prasetyo Hermawan; Titik Anggaraini (Politeknik ATK Yogyakarta, 2015)
The effort could be done to reduce formaldehid concentration in the water waste formaldehide glove snow white tannage are react formaldehide with H2O2 and NaHSO3. In this research, mol ratio to formaldTehide in two compound are variation (1: 0,5 , 1:1, 1:2 dan 1:3), then mixing about 1 hour where every 15 minutes we do sampling. The results are more greater mol ratio and time will give more formaldehide concentration could be reduced. From statistic models, shown that mol ratio 1: ½ to 1: 1 not significant in H2O2 compound, in mol ratio 1: 0,5 to 1:1 and 1:1 to1: 2 not significant in NaHSO3 compound. NaHSO3 have more abitllity to reduce formaldehide concentration than H2O2, in mol ratio to formaldehid 1: 3, in 60 minutes shown that 84% formaldehid reduced in NaHSO3 compound and 24% formaldehid reduced in H2O2 compound